A learning community approach to coach development in youth sport - Gilbert, W.; Gallimore, R.; Trudel, P. (Journal of Coaching Education, 2009)
Repeated calls have been made by prominent sport and education associations for the creation of ongoing professional development networks and learning communities for youth sport coaches. The purpose of this paper is to propose a learning community approach to coach development that complements large-scale coach education programs. This concept paper is organized into three sections followed by a brief summary. The three sections are: (a) overview of the effectiveness of community-based learning research on teacher development, (b) overview of how community-based learning literature has informed coach development initiatives, and (c) suggestions for how a learning community approach could be practically implemented in a typical youth sport setting.